2019
DOI: 10.3390/cancers11081144
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metabolism and the Evasion of Apoptotic Cell Death

Abstract: Cellular growth and proliferation depend upon the acquisition and synthesis of specific metabolites. These metabolites fuel the bioenergy, biosynthesis, and redox potential required for duplication of cellular biomass. Multicellular organisms maintain tissue homeostasis by balancing signals promoting proliferation and removal of cells via apoptosis. While apoptosis is in itself an energy dependent process activated by intrinsic and extrinsic signals, whether specific nutrient acquisition (elevated or suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 179 publications
(198 reference statements)
4
75
0
1
Order By: Relevance
“…We have learned from the literature that alterations in cellular metabolism pathways are manifest in cancer cells as compared to normal tissue cells [39][40][41].…”
Section: Cancer Metabolism and Cell Signalingmentioning
confidence: 99%
“…We have learned from the literature that alterations in cellular metabolism pathways are manifest in cancer cells as compared to normal tissue cells [39][40][41].…”
Section: Cancer Metabolism and Cell Signalingmentioning
confidence: 99%
“…it has been suggested that high levels of these eMT-TFs can also cause resistance to apoptosis by altering the TGF-β-and p53-mediated programmed cell death pathways (21)(22)(23)(24). Apoptosis is an energy-dependent mechanism of programmed cell death by which organisms maintain tissue homeostasis (25). Several pathways regulate apoptosis and several mechanisms are used by tumor cells to survive, suppressing apoptotic program.…”
Section: Discussionmentioning
confidence: 99%
“…The intrinsic pathway is altered in most cancer cells and is closely regulated by cellular metabolism. indeed metabolic changes occurring in cancer cells, consequent to oncogenic activation or stress-induced therapy, promote resistance to apoptosis and therapy via alterations of Bcl-2 family expression (25). P53, a protein often altered in tumor progression, has been implicated in the activation of the intrinsic and extrinsic pathways, and its ability to induce apoptosis depends on nF-κB activation (30).…”
Section: Discussionmentioning
confidence: 99%
“…The capability of sustained uncontrollable proliferation is a major feature of cancer cells. This feature is closely related to abnormalities of cell cycle regulation and mechanisms of apoptosis resistance [12][13][14]. Inhibiting the transition of cell cycle and inducing apoptosis of tumor cells have become a mature strategy and research direction for anti-tumor therapy, especially in HCC treatment [12,15,16].…”
Section: Introductionmentioning
confidence: 99%